1996
DOI: 10.3109/00365529609004881
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Bile Duct Calculi in Patients with Gallbladder in Situ Long-Term Outcome and Factors Predictive of Recurrent Symptoms

Abstract: These findings confirm that endoscopic treatment alone in this group of patients is a feasible treatment principle. Recognition of the registered risk factors might be helpful when selecting patients for subsequent cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 34 publications
2
28
0
2
Order By: Relevance
“…In the present study, the development of acute cholecystitis (17%) was more common than that of CBD stone (13%) recurrence after CBD stone removal. We believed that if the risk factors of acute cholecystitis in patients who receive an endoscopic CBD stone removal could be identified, we might be able to identify the indicators of prophylactic cholecystectomy, as has been mentioned by earlier investigators [13] . Some studies have compared the results of prophylactic cholecystectomy and non-surgical treatment [7,9,17] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the present study, the development of acute cholecystitis (17%) was more common than that of CBD stone (13%) recurrence after CBD stone removal. We believed that if the risk factors of acute cholecystitis in patients who receive an endoscopic CBD stone removal could be identified, we might be able to identify the indicators of prophylactic cholecystectomy, as has been mentioned by earlier investigators [13] . Some studies have compared the results of prophylactic cholecystectomy and non-surgical treatment [7,9,17] .…”
Section: Discussionmentioning
confidence: 90%
“…Because two patients in whom acute cholecystitis developed also experienced CBD stone recurrence and there was no case of cholangitis or CBD stricture, the overall recurrence rate of biliary-related events during follow-up after endoscopic CBD stone removal was 28% (28/100), which is similar to the rates of 5-24% reported www.wjgnet.com recent prospective [7] and large scale cohort studies [9] produced contrary conclusions concerning prophylactic cholecystectomy vs the wait-and-see approach. Moreover, because no consensus has been reached, the decision as to whether to operate or not is made empirically on a case-by-case basis [8,13,[17][18][19] . However, two important points should not be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Of those patients initially treated using ES, 35% required an additional cholecystectomy during the follow-up period. It is reported that 2% to 33% of patients with symptomatic choledocholithiasis require an additional cholecystectomy, suggesting that patients with ABP are at greater risk for late gallstone-related complications [75][76][77]. This also is supported by the observation that 15% of the patients from the Hammarstrom study required an emergency cholecystectomy after ES, compared with only 4% to 6% of patients presenting with symptomatic gallstone disease but not ABP [8,75].…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 91%
“…On the one hand, it is possible that advancing technology and overall improved quality of medical care allow for better outcomes, but on the other hand, more aggressive approaches in the elderly and in those patients with higher numbers of medical coexisting conditions might confer a worse prognosis. Public reports of complications and mortality rates after endoscopic biliary sphincterotomies mainly belong to the last decades of the twentieth century (3)(4)(5). Recent literature on the topic mostly focuses on comparing the outcomes after endoscopic biliary dilation vs endoscopic biliary sphincterotomies alone (6)(7)(8), but in our own experience the numbers of patients undergoing one or another procedure are very dissimilar.…”
Section: Introductionmentioning
confidence: 99%